Answers

2016-04-09T12:36:31+05:30
 \frac{3+ \sqrt{5} }{3- \sqrt{5} }  \frac{3- \sqrt{5} }{3+ \sqrt{5} }

 \frac{(3+ \sqrt{5} )^{2} + (3- \sqrt{5} )^{2} }{(3+ \sqrt{5} )(3- \sqrt{5})}

 \frac{(3+ \sqrt{5} )^{2} + (3- \sqrt{5} )^{2} }{3^{2}- \sqrt{5}^{2}   }

 \frac{3^{2}+ \sqrt{5}^{2}}{3^{2}- \sqrt{5}^{2}}

 \frac{9+5}{9-5}

 \frac{14}{4}

 \frac{7}{2}

3.5
0
ya
ok try
nope
my mom calling me
did u find any mistake in my answer
2016-04-09T17:28:52+05:30
 (3 + √5)/ ( 3 - √5) +( 3- √5)/ (3+ √5)
= (3+√5)² + (3 -√5)²    since [ (a+b)(a-b) =(a² -b²) ]
   (3² - (√5)² )
2( 3² +(√5)² )         since [  (a+b)² +(a-b)² = 2(a² + b²) ]
       9- 5
= 2( 9 + 5)
          4
= 2(14) / 4
= 28/ 4
= 7
0